Discursive Exposures of Exclusion through the Figure of the Traitor (Critical Romani Studies, 2025)
In this article, I present a historical conceptualization of the Hungarian-language term hazaáruló / traitor while contextualizingit within the emigration of Roma from Hungary to Canada and their subsequent return from Canada. I discuss how speakers emplaceRoma in Hungarian society through the figure of the hazaáruló / traitor, a term often employed in political debates to delegitimatizeopponents and also directed at Roma who returned from Canada, both by Roma and non-Roma. In tracing the concept historically,I take into account its legal definition and usage as codified in the Hungarian Criminal Code and contexts in which, for example, rulersoperationalized calls of treason as a linguistic device for disarming a political opponent (Cornwall 2015). Then, I describe a prominentcontemporary example of the discursive usage of the term hazaáruló / traitor in the case of the Roma from the town of Zámoly who fled Hungary to seek asylum in Strasbourg, France. Finally, I include relevant findings from ethnographic fieldwork during which Romani families frequently recounted instances of being named a hazaáruló / traitor for having migrated to Canada. In my analysis, I contend that the very act of Roma from Hungary seeking refuge were public exposures of the normalized relations of exclusion.
Keywords: Exclusion; forced return; racializing discourse; refugees; Roma; whiteness